Menghapus citra buruk njai dalam karya-karya fiksi berbahasa Melayu (1896-1927) - Sutedja-Liem, Maya (Wacana, Journal of the Humanities of Indonesia, 2008)
In the Dutch colonial literature of the mid nineteenth century, the njai (Asian concubine) is the symbol of degeneration and of undermining colonial society in the Dutch Indies. Opposed to this portrayal, in Malay literature the image of the njai is on the whole positive: she is faithful and loyal to her partner, intelligent, and economical. However, she easily falls victim to external powers, which is often the masculine power of the society she belongs to. In many Malay texts she is represented as ready to fight back, primarily for the sake of the future of her offspring(s) or herself. Sometimes she succumbs, sometimes she triumphs. Examples can be found in texts like Tjerita Njai Dasima (1896), Tjerita Nji Paina (1900), Seitang Koening (1906), Hikajat Raden Adjeng Badaroesmi (1901-1903), Tjerita Njai Isah (1904), and Boenga roos dari Tjikembang (1927). These texts represent a re-evaluation of the njai and stand in opposition to nineteenth century Dutch colonial literature.